Some Qualities of Ice for Consumption in Yala City Municipality - มุนินทร์นพมาศ วิภาดา; อามะ มิสบะห์; ดือราซอ ไซตน; มุนินทร์นพมาศ จีรวุธ (YRU Journal of Science and Technology, 2018)
The quality analysation of 3 types of ice in Yala municipality; ice-cube from manufacturers, crushed ice from manufacturers and crushed ice from distributors were compared with the quality of ice announced by the Ministry of Public Health. The 3 types of ice had the physical qualities in 100% standard. In the pH testing, 33.33% of ice-cube from manufacturer, 12.5% of crushed ice from manufacturer and 12.5% of crushed ice from distributor got the standard. In the solid quantity examination, 33.33% of ice-cube from manufacturer, 25.00% of crushed ice from manufacturer and 25.00% of crushed ice from distributor got the standard. Meanwhile, none of the ice had the hardness characteristic or in 100% standard. According to the coliforms quantity testing, 66.67% of ice-cube from manufacturer, 87.50% of crushed ice from manufacturer and 37.50% of crushed ice from distributor got the standard. In the fecal coliforms quantity testing, 66.67% of ice-cube from manufacturer, 87.50% of crushed ice from manufacturer and 37.50% of crushed ice from distributor got the standard. In the quantity examination of Escherichia coli, none of the ice-cube had the micro-organism, 87.50% of crushed ice from manufacturer and 50.00% of crushed ice from distributor got the standard.